2018
DOI: 10.1021/acsnano.8b02813
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Microenvironment by Bioreduction-Activated Nanoparticles for Light-Triggered Virotherapy

Abstract: Solid tumors characteristically display higher levels of lactate production due to anaerobic metabolism of glucose. Meanwhile, the U.S. Food and Drug Administration (FDA) has approved virotherapy for use in cancer treatment; however systemic administration remains as a particular challenge. Here we report exploitation of tumor lactate production in designing a hypoxia-responsive carrier, self-assembled from hyaluronic acid (HA) conjugated with 6-(2-nitroimidazole)­hexylamine, for localized release of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…gated to iron oxide NPs were remotely guided and delivered to the tumor site with microscale precision, where phototoxicity was then triggered by irradiation. 489,502,503 Recently, Tseng et al further developed this approach with an elaborate hybrid design. AAV encoding the photosensitive apoptosis-inducing protein was conjugated to SPIONs and loaded to a nitroimidazole conjugated hyaluronic acid NP containing lactate oxidase.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…gated to iron oxide NPs were remotely guided and delivered to the tumor site with microscale precision, where phototoxicity was then triggered by irradiation. 489,502,503 Recently, Tseng et al further developed this approach with an elaborate hybrid design. AAV encoding the photosensitive apoptosis-inducing protein was conjugated to SPIONs and loaded to a nitroimidazole conjugated hyaluronic acid NP containing lactate oxidase.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…This enzymatically-controlled release enabled targeted tumor cell lysis with an combinatorial approach of functional materials. 503 SPIONs are approved as contrast agents for magnetic resonance imaging, 504 which makes them a clinically promising vehicle for targeted delivery of VPs. One of main advantages of using magnetic NPs for VP delivery is the reduced vector dosage and short exposure times for efficient transduction due to controlled colocalization of cells and VPs.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…39,40,42 Interestingly, Mistry et al proposed a combinatory use of IONPs and nitrite, where the selective reconversion of nitrite to nitric oxide (NO) in hypoxia and low pH induced IONPs extravasation with important implications for the enhancement of conventional and nanotherapeutic drug delivery. 43 However, even though they have been loaded onto nano-sized systems as hypoxic tumor cytotoxins 44 or as inducers of hypoxia-responsive drug releasers, 45 small molecular bioreductive compounds have never been used to functionalize nano-vehicles and direct their interactions with cells. In the present study, we developed a novel metro-conjugated dendron to functionalize IONPs decorated with coating layers composed of biphosphonated dendrons and we preliminarily assessed their potential use in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al reported the preparation of a hypoxia-responsive carrier using the selfassembly of 6-(2-nitroimidazole)hexylamine-conjugated hyaluronic acid (HA) into which adeno-associated virus serotype 2 (AAV2)-conjugated ultrasmall iron oxide nanoparticles and lactate oxidase (LOX) were loaded. [19] Lactate within the tumor microenvironment could enter the carrier and be oxidized by LOX to increase the hypoxia level in the carrier, ultimately converting 6-(2-nitroimidazole)hexylamine into a hydrophilic moiety. As a result, the carrier dissociated, and the loaded small iron oxide nanoparticles were released.…”
Section: Small Nss With Detachable Shellsmentioning
confidence: 99%